Facile synthesis of g-CN/ATO hybrid nanocomposite and its application for the photodegradation of organic compounds - Prashad Ojha, Devi; Song, JunHee; Joo Kim, Han (International Journal of Engineering and Technology, 2018)
Photodegradation of organic pollutants using nanoparticles with suitable band gap is one of the most studied technologies in last few decades. About 6 nm antimony-doped tin oxide (ATO) nanoparticles, as the photocatalyst for organic degradation, is prepared by the calcination of the stoichiometric mixture of precursor hydroxides of Sn4+ and Sn3+. ATO was combined with thermally synthesized g-C3N4 and the resulting Z-scheme g-CN/ATO nanocomposite was utilized for the decomposition of salicylic acid (SA) in aqueous solution. All the samples were analyzed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR) and the progress of the photocatalytic degradation reaction was measured by using UV-Visible spectroscopy. The rate constant measurements showed that the rate of degradation of SA is enhanced with hybrid nanocomposite.Â